Quorum sensing intervened bacterial signaling: Pursuit of its cognizance and repression - Kayeen Vadakkan; Abbas Alam Choudhury; Ramya Gunasekaran; Janarthanam Hemapriya; Selvaraj Vijayanand (Journal of Genetic Engineering and Biotechnology, 2018)
Bacteria communicate within a system by means of a density dependent mechanism known as quorum sensing which regulate the metabolic and behavioral activities of a bacterial community. This sort of interaction occurs through a dialect of chemical signals called as autoinducers synthesized by bacteria. Bacterial quorum sensing occurs through various complex pathways depending upon specious diversity. Therefore the cognizance of quorum sensing mechanism will enable the regulation and thereby constrain bacterial communication. Inhibition strategies of quorum sensing are collectively called as quorum quenching; through which bacteria are incapacitated of its interaction with each other. Many virulence mechanism such as sporulation, biofilm formation, toxin production can be blocked by quorum quenching. Usually quorum quenching mechanisms can be broadly classified into enzymatic methods and non-enzymatic methods. Substantial understanding of bacterial communication and its inhibition enhances the development of novel antibacterial therapeutic drugs. In this review we have discussed the types and mechanisms of quorum sensing and various methods to inhibit and regulate density dependent bacterial communication. Keywords: Antibacterial agents, Autoinducers, Quorum quenching, Quorum sensing